Analysis of Sedgwick County Health Department school dental screening data to determine target areas for intervention - Hervey, Kaylee (My University, 2014)
Oral health is a critical aspect of child development, and dental decay is the most common chronic disease found in children. The goal of my capstone project with the Sedgwick County Health Department (SCHD) was to analyze school dental screening data from their Children’s Dental Clinic to determine areas for targeted interventions. Data collected from school dental screenings during the 2012 and 2013 calendar years were analyzed for percent untreated decay, percent emergency dental visit needed, percent of sealants present, and percent of sealants needed (dental variables). Descriptive variables were also created to further describe the study population (school district (USD), school level, location, predominant race, and percent of students who receive free lunch). The schools were ranked based on the ten highest and ten lowest schools for the dental variables. Following these rankings, logistic regression analysis was conducted to determine the associations between high untreated decay (≥13.9%) and low sealants present (<37.3%). When the schools were ranked based on the dental variables, schools with high levels of untreated decay and high levels of emergencies often had a high percent of students qualifying for free lunch. Schools with high levels of sealants present often had a low percent free lunch. This association was supported by correlation analysis. Univariate analysis indicated high levels of untreated decay was significantly associated with high emergency (≥3.5%), low sealants present, USD 259, school level elementary, predominant race of white, and high levels of free lunch (≥50%). A step-wise logistic regression model was developed to determine the association between high levels of untreated decay and the other variables. Based on this model, a school with low levels of sealants present was 22.48 (CI: 4.3-117.1) times as likely to be classified as a high percent untreated decay, when the effect of free lunch was considered. Based on the results of this study, the presence of dental sealants is associated with lower percentage of untreated dental decay in schools screened by the SCHD Children’s Dental Clinic. The SCHD plans to target the three schools with the highest percent of untreated dental decay using a parent survey to determine which interventions will best promote oral health in Sedgwick County children.
Keywords: Sedgwick County Kansas Health Department; Oral Health; Dental Decay; Dental Sealants; Public Health (0573)